Synthesis of nickel-rubber nanocomposites and evaluation of their dielectric properties - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2009)
Nanocomposites based on natural rubber and nano-sized nickel were synthesized by incorporating nickel nanoparticles in a natural rubber matrix for various loadings of the filler. Structural, morphological, magnetic and mechanical properties of the composites were evaluated along with a detailed study of dielectric properties. It was found that nickel particles were uniformly distributed in the matrix without agglomeration resulting ill a magnetic nanocomposite. The elastic properties showed an improvement with increase in filler content but breaking stress and breaking strain were found to decrease. Dielectric permittivity was found to decrease with increase in frequency, and found to increase with increase in nickel loading. The decrease in permittivity with temperature is attributed to the high volume expansivity of rubber at elevated temperatures. Dielectric loss of blank rubber as well as the composites was found to increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dielectric relaxation; Interfacial polarization; Nanocomposites

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites

Magnetic and electric responsive hydrogel-magnetic nanocomposites for drug-delivery application - Reddy, N. Narayana; Mohan, Y. Murali; Varaprasad, K.; Ravindra, S.; Joy, Pattayil Alias; Raju, K. Mohana (Journal of Applied Polymer Science, 2011)
Magnetic and electrically responsive hydrogel networks were developed for drug-delivery applications. The hydrogel matrices were synthesized by the polymerization of acrylamide monomer in the presence of carboxymethylcellulose (CMC) or methylcellulose (MC) with N,N-methylenebisacrylamide, a crosslinker with the redox initiating system ammonium persulfate/tetramethylethylenediamine. The magnetic nanoparticles were generated throughout these hydrogel matrices by an in situ method by the incorporation of iron ions and their subsequent reduction with ammonia. A series of hydrogel-magnetic nanocomposites (HGMNCs) were developed with various CMC and MC compositions. The synthesized HGMNCs were characterized with spectral (Fourier transform infrared and ultraviolet-visible spectroscopy), X-ray diffraction, thermal, and microscopy methods. These HGMNCs contained iron oxide (Fe3O4) nanoparticles with an average particle size of about 22 nm, as observed by transmission electron microscopy. The dielectrical properties of the pure hydrogel (HG); the hydrogel loaded with iron ions, or the hydrogel iron-ion composite (HGIC); and the HGMNCs were measured. These results suggest that HGMNCs exhibited higher dielectric constants compared to HG and HGICs. The curcumin loading and release characteristics were also measured for HG, HGIC, and HGMNC systems. These data revealed that there was a sustained release of curcumin from HGMNCs because of the presence of magnetic nanoparticles in the hydrogel networks. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1364-1375, 2011
Keywords: hydrogels; magnetic polymers; Nanocomposites; nanoparticle; nanotechnology